STP technology for global financial services: critical success factor, implementation model, and case study. (2016) - Cai, H.L.; Chen, Yining; Liu, Yuewen; Shen, Huizhang; Zhang, Tan
For the last decade, straight through processing (STP) has been a catch phrase in the securities markets, reflecting the industry's continued pursuit of moving electronically through a trading process from initiation through post-execution and final settlement without manual intervention. To bring forth the full benefits of STP, this study presents a conceptual framework that takes into consideration the distinction between internal processes and external processes as well as the integration level and connectivity between the two types of processes. Cumulative benefits from the implementation of such a conceptual framework are discussed. Moreover, this study identifies two clusters of critical success factors (CSFs) and four suitable models to guide STP implementation practice. Case studies in the end exemplify benefits attained from implementing STP with sensible consideration of CSFs and proper application of implementation models.